Domestic injuries among infancy: a prospective descriptive study - Gupta, Ravinder K.; Gupta, Ritu; Bhadwal, Abhai S.; Sharma, Vikas (International Journal of Contemporary Pediatrics, 2021)
Background: Injuries in the form of accidents are a major cause of morbidity and mortality in children. The objective of this study was to determine the prevalence of different types and modes injuries among the infants. Methods:A prospective study data from two hundred infants who visited the pediatric OPD in a private pediatric clinic following injury was recorded. A pre-structured questionnaire was provided to the parents. Health education was imparted to the parents regarding prevention of such injuries. Results: Among 200 infants under study, most of the infants were between 8-12 months. Fall being the most common type of injury and it was mostly due to walkers. The most common site of injury was the forehead. Conclusions:Structural modifications are required to be made in the home along with parent education by pediatrician, by doing this most of the injuries can be prevented.